PENGARUH KUALITAS PELAYANAN, KOMUNIKASI TERAPEUTIK DAN AKSESBILITAS TERHADAP KEPUASAN PASIEN DI PUSKESMAS TANGGETADA KABUPATEN KOLAKA - Soharab, Tri Asmitasari (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This research aims to analyze the effect of therapeutic Communication, service quality and patient satisfaction against aksesbilitas in Kolaka Tanggetada Clinics. The source data used using questionnaires and then analyzed using analysis data processing with SPSS 23. The results obtained from the research shows the value of F count of significance and value of 36,861 0.000 < α (0.05) stated the influence of therapeutic communication, service quality and patient satisfaction against aksesbilitas in Clinics Tanggetada Kolaka Regency.